Pendampingan Penyusunan Laporan Harga Pokok Produksi Pempek Sentosa - Maria Maria; Yevi Dwitayanti; Desi Indriasari; Nurhasanah Nurhasanah; Rabbiyati Ningsi (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) Sentosa Palembang process and sell various pempek. As a business that carries out production activities, Sentosa MSMEs require calculating the Cost of Goods Produced (COGS) which is the basis for determining the selling price. This has not been done by MSMEs Pempek Sentosa. So far, business owners determine production costs using only estimates so that they have not reflected the proper conditions. For this reason, counseling and assistance in determining COGS in MSMEs are carried out. With this activity, business owners can find out the costs incurred for making pempek so that the selling price and the desired profit achievement are measured.